2003
DOI: 10.1016/s0926-860x(02)00372-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimized palladium catalyst systems for the selective liquid-phase hydrogenation of functionalyzed alkynes

Abstract: Silica-supported palladium catalysts for the selective liquid-phase hydrogenation of alkynes to alkenes were prepared. As a model reaction the hydrogenation of 3-methyl-1-pentyn-3-ol was chosen. The kinetics of this reaction were investigated. Different approaches were used to obtain an optimal catalyst system. The selectivity of the palladium catalysts was successfully improved by modifying the catalyst with copper and the effect of this modification on the reaction mechanism was studied. The addition of quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 16 publications
2
69
0
3
Order By: Relevance
“…As previously mentioned the Lindlar catalyst contains electrondeficient palladium species. Nijhuis et al 41 have found that palladium modified with Pb(OAc) 2 during the Lindlar catalyst preparation gets electron deficient and that this electron deficiency enhances the Pd-alkyne interaction. It should be also considered that 1-heptene is adsorbed more weakly than 1-heptyne on these species.…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned the Lindlar catalyst contains electrondeficient palladium species. Nijhuis et al 41 have found that palladium modified with Pb(OAc) 2 during the Lindlar catalyst preparation gets electron deficient and that this electron deficiency enhances the Pd-alkyne interaction. It should be also considered that 1-heptene is adsorbed more weakly than 1-heptyne on these species.…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst was stored in a nitrogen atmosphere. The detailed recipe for this preparation can be found in [4]. Hydrogenation experiments were performed in glass slurry-reactor at 298 K and 1 bar pressure with (dry) ethanol as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in the selectivity at a higher pressure might be ascribed either to (i) the mass transfer limitations or (ii) an increased MBY to MBA reaction rate, which is proportional to squared hydrogen pressure. The mass transfer limitations may lead to a slow removal of MBE molecules from the catalyst vicinity, and result in overhydrogenation [29]. There are three possible mechanisms for the masstransfer limited operation: external mass transfer, gas-liquid mass transfer, or internal diffusion in the catalyst.…”
Section: Effect Of Liquid Flow Ratesmentioning
confidence: 99%